Stalking the Riemann hypothesis the quest to find the hidden law of prime numbers - Rockmore, Daniel N. 1961- (Pantheon Books, 2005)
"Stalking the Riemann Hyothesis" takes you on a guided tour of the deepest mystery in mathematics.
Includes index.
Keywords: Riemann, Bernhard <1826-1866>; aRiemann, Bernhard -- d1826-1866; Riemann, Bernhard -- 1826-1866; Nombres premiers; Nombres, Théorie des; Riemann, Hypothèse de; aNumbers, Prime; aNumber theory; Primzahltheorie